2019
DOI: 10.3390/polym11091407
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Interfacial Friction Heating in Polymer Ultrasonic Plasticization Injection Molding Process

Abstract: Ultrasonic Plasticization Injection Molding (UPIM) is an effective way to manufacture polymeric micro parts and has great potential for energy saving with processing polymeric materials of a small amount. To better control the UPIM process and improve the quality of micro parts, it is necessary to study the heat generation mechanism. In this paper, the interfacial friction heating process of UPIM was studied by finite element (FEM) simulation and experiment, and the temperature change in the friction interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Compared with the experimental results of trigger pressure, the height of PP, PA66, and PMMA samples decreased by 43.1%, 49.8%, and 47.3%, respectively, the influence of plasticizing pressure can be sequenced as PMMA ≈ PA66 > PP. The possible reason for the above results was that the temperature of the contact area of the pellet increases rapidly under interfacial friction [19,21,22]. The pressure of sonotrode makes the softened polymer fill the gap, the contact state of inter-pellets changes from point contact to face contact meanwhile.…”
Section: Height Of Plasticized Samplementioning
confidence: 95%
See 2 more Smart Citations
“…Compared with the experimental results of trigger pressure, the height of PP, PA66, and PMMA samples decreased by 43.1%, 49.8%, and 47.3%, respectively, the influence of plasticizing pressure can be sequenced as PMMA ≈ PA66 > PP. The possible reason for the above results was that the temperature of the contact area of the pellet increases rapidly under interfacial friction [19,21,22]. The pressure of sonotrode makes the softened polymer fill the gap, the contact state of inter-pellets changes from point contact to face contact meanwhile.…”
Section: Height Of Plasticized Samplementioning
confidence: 95%
“…Michaeli believes that the energy source of ultrasonic plasticization mainly comes from frictional heat and viscoelastic heat, similar to ultrasonic welding [18]. We studied the mechanism of frictional heat generation and viscoelastic heat generation [19][20][21][22] and found that the interfacial frictional heat determines the temperature distribution during the initial stage of ultrasonic plasticization. Interfacial friction heat generation is the main energy source when the polymer pellets are at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the wide application of micro/nanodevices, polymer micro/nano manufacturing technology has gradually become one of the important research directions. [1][2][3] Commonly used polymer micro/nano manufacturing technologies include micro-injection molding, 4 nanoimprint lithography, 5 microextrusion molding, 6 etc. Among them, microinjection molding has attracted the attention of many researchers because of its advantages, such as short manufacturing cycle, high efficiency, and mass production potential.…”
Section: Introductionmentioning
confidence: 99%
“…In micro-UPM, ultrasonic vibration was applied to the polymer pellets [ 25 , 26 ]. Under the effect of the ultrasonic vibration, friction between the polymer pellets could take place and, thus, the heat can be generated for fabricating the microplastic parts, which has high forming efficiency [ 27 , 28 ]. During micro-UPM, the heating time of polymer material is short, which avoids the degradation of the polymer.…”
Section: Introductionmentioning
confidence: 99%